UNIFIATION OF SYSTEMS OF FINANCIAL AND MANAGEMENT ACCOUNTS: COHERENT-KOGEZYNY MODIFICATION OF THE ENERGY SAVINGS PROGRAM OF THE ENTERPRISE - Klimchuk , M.M. (The actual problems of regional economy development, 2018)
The problems of unification of managerial and financial accounting on the basis of the concept of integrated reporting through the principle of the integrity of the economic and analytical support of the implementation of energy saving programs of the enterprise are investigated. It is determined that one of the main factors that has a significant impact on the level of efficiency of the energy saving management system of the enterprise is economic and analytical support. The coherent-cohesive model of economical and analytical provision of the energy saving management system at the enterprise is presented, which will provide an opportunity to create a common information space for stakeholders.